A fuzzy system with ?-insensitive learning of premises and consequences of if-then rules - Łęski, Jacek M.; Czogała, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
First, a fuzzy system based on if-then rules and with parametric consequences is recalled. Then, it is shown that the global and local ?-insensitive learning of the above fuzzy system may be presented as a combination of both an ?-insensitive gradient method and solving a system of linear inequalities. Examples are given of using the introduced method to design fuzzy models of real-life data.
Keywords: fuzzy systems; generalization ability; extraction of fuzzy if-then rules